Babatha's orchard: the yadin papyri and an ancient Jewish family tale retold - Esler, Philip Francis (Oxford University Press, 2017)
Babatha's Orchard' tells a story that has gone untold for nearly two thousand years. It is a story that would have perished with the last person familiar with its details-the Jewish woman Babatha, daughter of Shim'on ben Menahem. Babatha was probably killed or enslaved by Roman soldiers at the end of Shim'on ben Kosiba's revolt in 135 CE, when they captured a cave in a wadi running into the western shores of the Dead Sea in which she and other Jewish fugitives had been sheltering. In 1961, a team of archaeologists discovered a cache of possessions that Babatha had carefully hidden before her life or freedom was probably taken by the Romans. Among them were thirty-five legal documents dated from 94 CE to 132 CE, written on papyrus in Aramaic and Greek, relating to Babatha and her family, and the leather pouch in which they had been kept